Air pollution effects on myocardial infarction Efeitos da poluição do ar no infarto do miocárdio - Sônia Cendon; Luiz A A Pereira; Alfésio L F Braga; Gleice M S Conceição; Abraão Cury Junior; Hélio Romaldini; Antônio C Lopes; Paulo H N Saldiva (Universidade de São Paulo, 2006)
OBJECTIVE: Myocardial infarction is an acute and severe cardiovascular disease that generally leads to patient admissions to intensive care units and few cases are initially admitted to infirmaries. The objective of the study was to assess whether estimates of air pollution effects on myocardial infarction morbidity are modified by the source of health information. METHODS: The study was carried out in hospitals of the Brazilian Health System in the city of São Paulo, Southern Brazil. A time series study (1998-1999) was performed using two outcomes: infarction admissions to infirmaries and to intensive care units, both for people older than 64 years of age. Generalized linear models controlling for seasonality (long and short-term trends) and weather were used. The eight-day cumulative effects of air pollutants were assessed using third degree polynomial distributed lag models. RESULTS: Almost 70% of daily hospital admissions due to myocardial infarction were to infirmaries. Despite that, the effects of air pollutants on infarction were higher for intensive care units admissions. All pollutants were positively associated with the study outcomes but SO2 presented the strongest statistically significant association. An interquartile range increase on SO2 concentration was associated with increases of 13% (95% CI: 6-19) and 8% (95% CI: 2-13) of intensive care units and infirmary infarction admissions, respectively. CONCLUSIONS: It may be assumed there is a misclassification of myocardial infarction admissions to infirmaries leading to overestimation. Also, despite the absolute number of events, admissions to intensive care units data provides a more adequate estimate of the magnitude of air pollution effects on infarction admissions. OBJETIVO: O infarto do miocárdio é uma doença cardiovascular grave que tem como indicação a internação em unidades de terapia intensiva, com poucos indicados para admissão em enfermarias. O objetivo do estudo foi investigar se as estimativas dos efeitos da poluição atmosférica nas internações por infarto do miocárdio são modificadas de acordo com a fonte de informações de saúde. MÉTODOS: Em hospitais do Sistema Único de Saúde (SUS), na cidade de São Paulo, foi realizado estudo de séries temporais (1998-1999) tendo como desfechos as internações por infarto em unidades de terapia intensiva e em enfermarias, em pessoas acima de 64 anos. Foram utilizados modelos lineares generalizados, controlados para sazonalidade (de longa e curta duração) e variáveis climáticas. Foram construídos modelos distribuídos de defasagem polinomial de terceiro grau, para avaliar os efeitos acumulados nos oito dias anteriores à exposição. RESULTADOS: Aproximadamente 70% das internações por infarto no miocárdio ocorreram em enfermarias. Apesar disso, os efeitos da poluição sobre os casos foram maiores nas internações em unidades de terapia intensiva. Todos os poluentes mostraram uma associação positiva com os desfechos, mas o SO2 apresentou uma associação mais robusta e estatisticamente significante. O aumento do intervalo interquartil para as concentrações observadas do SO2 foi associado ao aumento em 13% (IC 95%: 6-19) e 8% (IC 95%: 2-13) nas internações em unidade de terapia intensiva e enfermarias, respectivamente. CONCLUSÕES: Pode-se supor que exista um erro de classificação das internações por infarto nas enfermarias, superestimando o número de internações. No entanto, o menor número de internações por infarto do miocárdio em unidades de terapia intensiva, é o indicador mais adequado para estimar os efeitos da poluição atmosférica nas internações por infarto.